Evaluating patient harm minimization during the COVID-19-driven reduction in benign gynecological care: a nationwide claims-based longitudinal study in the Netherlands - Eva L.M. Velthuijs; Ismail Ismail; Robert A. de Leeuw; Wouter J.K. Hehenkamp; Xander H.E. Koolman (PLoS ONE, 2026)
Objective To evaluate whether the COVID-19 pandemic influenced treatment modality, care intensity, and care setting in benign gynecological care in the Netherlands. Design Retrospective longitudinal cohort study evaluating the effects of the COVID-19 pandemic. Setting Nationwide healthcare delivery was analyzed across four benign gynecological pathways from 2017 to 2022 using Vektis and Dutch Hospital Data (DHD), accessed via Statistics Netherlands (CBS). Participants The study focused on four benign gynecological pathways, classified using Dutch Diagnosis Treatment Combinations (DTCs): menstrual disorders (G11), uterine fibroids (G15), prolapse (G25), and first-trimester pregnancy complications (Z12). All patients with a new DTC in the first half of each year were included. Exclusion criteria were patients under 18 years, and only in the menstrual disorder pathway, patients over 51 years of age. Intervention or exposure Cohorts from the initial pandemic year (2020) were compared to pre-pandemic years (2017–2019), the late pandemic year (2021), and the post-pandemic year (2022). Main outcomes and measures The primary outcome was the change in treatment mix within the care pathways. Secondary outcomes included regional variation, hospital-type distribution and care intensity. Results In 2020, all care pathways showed reduced unique patient volumes. Treatment mix did change during the COVID-19 pandemic, but not uniformly across the four pathways toward more less-invasive options. We found no regional differences in treatment mixes. Patient age, number of care activities and medication use remained stable. Telephone follow-up consultations increased markedly in 2020. No deviation from the trend was observed in respect of hospital type providing care. Conclusions and relevance A sharp reduction in benign gynecological care did not result in strategies to minimize patient harm like prioritization or substitution of care, as observed with our available claims data. Our findings indicate a lack of flexibility in health care provision to adjust to rapidly changing demands. Data limitations underscore the need for complementary research using other data sources to assess patient harm.